-16g-20g+(-7g)-(-2g)=19

Simple and best practice solution for -16g-20g+(-7g)-(-2g)=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16g-20g+(-7g)-(-2g)=19 equation:


Simplifying
-16g + -20g + (-7g) + -1(-2g) = 19

Remove parenthesis around (-2g)
-16g + -20g + (-7g) + -1 * -2g = 19

Multiply -1 * -2
-16g + -20g + (-7g) + 2g = 19

Combine like terms: -16g + -20g = -36g
-36g + (-7g) + 2g = 19

Combine like terms: -36g + (-7g) = -43g
-43g + 2g = 19

Combine like terms: -43g + 2g = -41g
-41g = 19

Solving
-41g = 19

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '-41'.
g = -0.4634146341

Simplifying
g = -0.4634146341

See similar equations:

| 7t-t-8=5t-6 | | 8x+19+21x-13=180 | | 8m+3=-5 | | 10x+1+4x+11=180 | | 7x+25+17x-13=180 | | 4+(x)+5=7 | | k/5-10=-3 | | a+6+5+11=4a+1 | | (5y+20)-(6y-2)=26 | | (75+50)x=(25+70)x | | 7x+25=17x-13 | | 6x-11=9x-53 | | 75x-50=25x-70 | | a+9=-30 | | 3x+4(5x-16)=97 | | -4u+u-8u-(-2u)=(-9) | | 3x+4(5z-16)=97 | | 4x+15=10x-33 | | (2/c-2)=2-(4/c) | | slope-3-x=3y | | 25/12= | | 3-6x+8x=6 | | 12/x+5=6/2x+8 | | 0.10(x+5)=2.4 | | 0.10(x+5)=2 | | 10x-5=-13 | | -116-12x=8 | | 2cos^3x+cos^2x-2cosx-1=0 | | 10c^2-10c^3= | | 7/4a=-14 | | 3x-9=57 | | 50/2= |

Equations solver categories